2021
DOI: 10.5534/wjmh.190095
|View full text |Cite
|
Sign up to set email alerts
|

Standard Semen Parametersvs.Sperm Kinematics to Predict Sperm DNA Damage

Abstract: Purpose: The aims of this study were to associate sperm kinematics and standard semen parameters with sperm DNA damage and to evaluate whether the addition of sperm kinematics improve the multivariable prediction of sperm DNA fragmentation compared to standard semen parameters alone. Materials and Methods: We evaluated sperm kinematics, standard semen parameters, and DNA fragmentation index (DFI) in 122 men. Univariate and multivariate logistic regression models were fitted to evaluate the association of sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In another study, among 272 infertile men who sought for treatment SDF evaluated by TUNEL was found to be negatively correlated with sperm concentration, progressive motility but not correlated with normal morphology (Amor, Shelko, Hamad, Zeyad, & Hammadeh, 2019). Also some studies showed a strong relationship between vitality and SDF (Aghazarian, Huf, Pfluger, & Klatte, 2019. The differences in the number and features of selected patient groups may have caused this confliction between the results.…”
Section: Discussionmentioning
confidence: 96%
“…In another study, among 272 infertile men who sought for treatment SDF evaluated by TUNEL was found to be negatively correlated with sperm concentration, progressive motility but not correlated with normal morphology (Amor, Shelko, Hamad, Zeyad, & Hammadeh, 2019). Also some studies showed a strong relationship between vitality and SDF (Aghazarian, Huf, Pfluger, & Klatte, 2019. The differences in the number and features of selected patient groups may have caused this confliction between the results.…”
Section: Discussionmentioning
confidence: 96%
“…Aghazarian et al 33 showed that sperm vitality is independently associated with SDF when analysed by the SCD test and that vitality is the strongest predictor of damaged sperm DNA (Area Under Curve = 0.833, 95% CI = 0.815; 0.95). Homa et al 34 focused on the relationship between seminal oxidative stress with SDF and vitality.…”
Section: Consequence Of Necrozoospermia On the Sperm's Inherent Qualitymentioning
confidence: 99%
“…2 Decreased sperm vitality is often associated with higher rates of SDF. [32][33][34][35] Samplaski's team 4,32 reported a correlation between the degree of necrozoospermia and the rates of SDF.…”
Section: Consequence Of Necrozoospermia On the Sperm's Inherent Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Specific sperm kinematic factors are also taken into consideration when performing c-IVF. Among those, sperm curvilinear velocity (VCL), straight-line velocity (VSL), average path velocity (VAP) and amplitude of lateral head displacement (ALH), measured using computer-assisted analysis, have been shown to be efficiently able to anticipate c-IVF outcome [ 126 ]. VSL and VCL could be implemented as a prognostic value in order to predict the fertilization potential of the semen sample.…”
Section: Conventional Ivf and Male Gametesmentioning
confidence: 99%